Academic Study of Indonesian Islam: A Biographical Account, 1970-2014 - Karel A Steenbrink (Al-Jami'ah Research Centre, 2015)
In the humanities, including religious studies, personal factors often play a role in the selection of topic and methodology of research. This autobiographical sketch gives an overview of a long career in the study of religion in Indonesia, from the selection of the topic for doctoral research, through various jobs and academic projects until some work written in a period of retirement. The author’s background of liberal Catholicism with much interest in non-official popular religiosity, has influenced an approach in Islamic Studies and a selective attention for the boundaries between official and more popular religiosity, for literary and artistic expressions rather than for rigid doctrinal traditions. This history is told from field work to pesantren education in the early 1970s, the variety of Islamic history of Indonesia in the 1980s, until a major work in three volumes on the Catholic traditions of Indonesia in the period 1990-2010.[Dalam ilmu humaniora, termasuk studi keagamaan, faktor-faktor pribadi sering mempengaruhi pemilihan topik dan metodologi penelitian. Uraian biografis ringkas ini menggambarkan perjalanan panjang sebagai peneliti agama di Indonesia, mulai dari pemilihan topik riset disertasi, melewati beragam pekerjaan dan proyek-proyek akademik, sampai dengan beberapa karya yang ditulis sesudah pensiun. Latar belakang penulis sebagai penganut Katolik liberal dan banyak tertarik pada keberagamaan populer non-resmi, mempengaruhi pendekatan dalam pengkajian Islam dan perhatian khusus pada batas-batas antara agama resmi dan agama populer, pada ungkapan-ungkapan sastrawi dan seni daripada tradisi-tradisi doktriner yang kaku. Kisah ini berangkat dari pengalaman penelitian lapangan di lingkungan pendidikan pesantren pada tahun 1970an, kemudian serpihan-serpihan sejarah Indonesia pada tahun 1980an, sampai dengan penulisan tiga jilid buku penting tentang tradisi-tradisi Katolik Indonesia pada tahun 1990-2010.]